ATTITUDES AND EXPERIENCES OF LECTURERS WITH E-ASSESSMENT - Jahodová Berková, Andrea (International Association of Technology, Education and Development (IATED), 2019)
E-assessment is increasingly used in education especially at university level. The undergraduate mathematics courses are no exception. The aim of the research has consisted in finding out the attitudes and experiences of lecturers (teachers / instructors) regarding the use of e-assessment in their teaching. For this reason, e-assessment system was implemented into the teaching of undergraduate courses of Mathematical Analysis, Geometry and Algebra. Experience of members of the Department of Mathematics (lecturers) with teaching with the aid of the e-assessment system was followed by the semi-structured interviews with them. Interviews were recorded and transcribed for qualitative analysis through coding and categorizing. Despite the fact that the respondents evaluated the use of the e-assessment system positively, they specifically identified many shortcomings (including stress and lack of support). The presented results are part of more extensive research which also includes identifying students' attitudes and experiences. Some partial results of this research have been presented earlier in previous conferences.
Postoje a zkušenosti lektorů s elektronickým hodnocením.
Keywords: mathematics education; výuka matematiky; assesment in mathematics; e-assesment; computer-aided assessment; hodnocení matematiky; elektronické hodnocení; počítačové hodnocení